A mathematical-epidemiological model of obesity control - López Cruz, Roxana (2020)
In this work, we analyze the stability of two epidemiological models of obesity. The first model only admits social influence, that is, the environment in which individuals live, the second model adds control to reduce obesity and excess weight. The obesity-free equilibrium point is local and asymptotically stable if R0 < 1 where R0 is a basic replacement rate. For the model with control, its stability is shown and it is appreciated numerically that it accelerates the decrease of obese individuals.